2018
DOI: 10.1038/s41537-018-0064-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different types of cognitive enhancers for patients with schizophrenia: a meta-analysis

Abstract: Cognitive impairment is a core feature of schizophrenia, which is predictive for functional outcomes and is, therefore, a treatment target in itself. Yet, literature on efficacy of different pharmaco-therapeutic options is inconsistent. This quantitative review provides an overview of studies that investigated potential cognitive enhancers in schizophrenia. We included pharmacological agents, which target different neurotransmitter systems and evaluated their efficacy on overall cognitive functioning and seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 129 publications
2
43
0
3
Order By: Relevance
“…Cognitive deficits are a lifelong burden for patients with schizophrenia because there are so few effective medications including mainstay anti-dopaminergic agents (37,77). In line with the notion that dopaminergic dysfunction alone doesn't account for the whole picture of schizophrenia psychopathology (78,79), here we revealed that the networks and nodes predictive of individual cognitive symptom-load are related to both dopaminergic (32) and serotonergic systems (78).…”
Section: Molecular Architecture Of the Network Robustly Predicted Cosupporting
confidence: 76%
“…Cognitive deficits are a lifelong burden for patients with schizophrenia because there are so few effective medications including mainstay anti-dopaminergic agents (37,77). In line with the notion that dopaminergic dysfunction alone doesn't account for the whole picture of schizophrenia psychopathology (78,79), here we revealed that the networks and nodes predictive of individual cognitive symptom-load are related to both dopaminergic (32) and serotonergic systems (78).…”
Section: Molecular Architecture Of the Network Robustly Predicted Cosupporting
confidence: 76%
“…Cognitive deficits are a lifelong burden for patients with schizophrenia because there are so few effective medications including the mainstay anti-dopaminergic agents (37,77). In line with the notion that dopaminergic dysfunction alone doesn't account for the whole picture of schizophrenia psychopathology (78,79), here we revealed that the networks and nodes predictive of individual cognitive symptom-load are related to both dopaminergic (32) and serotonergic systems (78).…”
Section: Molecular Architecture Of the Identified Network Which Robusupporting
confidence: 80%
“…Despite considerable efforts across dozens of studies, these agents have not been consistently successful in improving cognition and functioning. Overall, a recent meta‐analysis reported that across all available studies (n=93) there was a significant, though quite small (Hedges’ g=0.10), effect for overall cognition, with no significant effects for any cognitive subdomain.…”
Section: Interventions For Cognitive Impairmentsmentioning
confidence: 99%